Propagação assexuada de chacrona (psychotria viridis ruiz & pavon) via estaquia foliar - Salgado, Moisés Pereira Galvão; Furlan, Marcos Roberto [UNESP]; Aoyama, Elisa Mitsuko [UNESP]; Rodrigues, Eliana; Cruz, Lilian Pereira (My University, 2012)
This study aimed to assess the asexual propagation of Psychotria viridis by leaf cuttings. The treatments were: A - Whole leaf cuttings, B - leaf cuttings with the top third cut off; C - with the lower third of the cuttings removed; D - with cuts on the primary vein of leaf cuttings, and E - poles with cuts on the leaf's secondary veins. The cuttings were immersed in distilled water for a period of 70 days. In all the treatments, the rooting was observed to occur in the region of the cut, or the place where the incision in the vein was. Current assay shows the feasibilities of Psychotria viridis leaf stalks and concludes that cuttings at the nerve ends highlight rooting in so far as the leaf stalks remain in permanent contact with the plant.
Asexual propagation of psychotria viridis (ruiz & pavon) via leaf cutting
Keywords: Medicinal plant; Ritualistic plant; Rooting; Rubiaceae; Pavon; Psychotria; Psychotria viridis